Study of Prototype Making of Liquid Smoke Production Equipment From Tree Trunk Waste and Used Wood - Tjahjanti, Prantasi Harmi; Bachtiar, Rifky Umar (Community Development Journal, 2024)
Making use of natural trash is crucial. Examples of such garbage include maize cobs, worn wood, and tree trunks. As part of this community service project, used wood and tree trunk waste will be used as raw materials to create prototype tools for producing liquid smoke. The process starts with tool design and ends with tool construction. A conical tube-shaped pyriolysis device is part of the liquid smoke production apparatus, and it is linked to a connecting pipe through which it is connected. The installation of an ionometer, storage container, gas exhaust hose, and bierate fraction sedimentation tube follows. The effective capacity of the apparatus, the temperature increase rate test during the pyrolysis process, the yield test, the charcoal weight test from the combustion residue, and the temperature increase rate test during the distillation process were among the equipment performance tests that were conducted. The findings showed that: (1) this pyrolysis device's average effective capacity was 0.5 L/hour; (2) the yield was 35.34%; and (3) experiment 3 produced the maximum output of liquid smoke, at 1.9 L, while experiment 2 produced the lowest yield, at 1.65 L. (5) The computation yielded a density value of 1.01 kg/L for liquid smoke; (6) Three attempts of pyrolysis combustion with a pyrolysis tool produced 4.3 kg of residue (carbon) or charcoal. (7) From 1000 mL of liquid smoke to be distilled, 400 mL of liquid smoke was obtained after 80 minutes of distillation.